PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR SISWA MATERI PANTUN PADA MATA PELAJARAN BAHASA INDONESIA - Harahap, Asriana; Harahap, Nurul Khafifah (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2023)
This research was motivated by the low learning outcomes of class V students at SD Negeri 0301 Sokopan in the Indonesian language subject, pantun material due to the teacher's ineffectiveness in using innovative learning models in the learning process. This research aims to determine the significant influence of using the Make a Match learning model on student learning outcomes in rhyme material in class V of SD Negeri 0301 Sosopan. This type of research is descriptive quantitative. The research population was all class V students, totaling 20 students. The sampling technique used was total sampling. Based on data analysis, it was obtained that (1) An overview of the use of the Make a Match learning model in rhyme material in class V of SD Negeri 0301 Sosopan obtained student response questionnaire results in the high category with a score of 90%. (2) Description of student learning outcomes for pantun material in class V of SD Negeri 0301 Sosopan using the Make a Match learning model, obtained an average score of 43 in the